The Benefits and Challenges of Blockchain Technology and eHealth Implementation in Estonia - A Literature Review - Bruno SOARES; António FERREIRA; Pedro MOTA VEIGA (Applied Medical Informatics, 2023)
This study aimed to review the existing literature on the benefits and challenges of the implementation of digital eHealth systems, using the success story of Estonia; and explores the impact of blockchain technology in facilitating eHealth adoption. By using the search query string “Estoni*” and (“eHealth” OR “e-Health” OR “Blockchain”) on the Scopus database (on April 2023) a narrative review was conducted over the relevant peer-reviewed publications written in English. The Scopus database and its integrated search engine presented 74 publications of which 18 filled the selected criteria. Access, efficiency, quality of care, cooperation and data sharing, knowledge, and control were among the most mentioned benefits of eHealth. Disparities, confidentiality lack of trust, financing, the cognitive burden, and the quality of data were the most mentioned challenges of implementing digital technologies in healthcare. This research provides an extensive up-to-date review of the benefits and challenges of the implementation of eHealth on a nationwide level, whilst analyzing the impact of blockchain technology. The article brings attention to the potential future applications of eHealth developments such as Computerized Decision Support Systems and cross-border healthcare.